Globalization and Cultural Identity in Australia - Senjov-Makohon, N. (Народна творчість та етнологія, 2019)
The article is dedicated to the cultural identity and globalization of Ukrainians who have arrived in Australia from two distinct areas of Europe to form a Ukrainian community, which has existed there for over 70 years.